2015
DOI: 10.3389/fpls.2015.00677
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling and functional analysis reveals that TOR is a key player in regulating photosynthesis and phytohormone signaling pathways in Arabidopsis

Abstract: Target of rapamycin (TOR) acts as a master regulator to control cell growth by integrating nutrient, energy, and growth factors in all eukaryotic species. TOR plays an evolutionarily conserved role in regulating the transcription of genes associated with anabolic and catabolic processes in Arabidopsis, but little is known about the functions of TOR in photosynthesis and phytohormone signaling, which are unique features of plants. In this study, AZD8055 (AZD) was screened as the strongest active-site TOR inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
221
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(245 citation statements)
references
References 48 publications
16
221
0
8
Order By: Relevance
“…Several studies have investigated the impact of TOR inhibition in Arabidopsis on transcript or metabolite levels (Deprost et al, 2007; Moreau et al, 2012; Caldana et al, 2013; Xiong et al, 2013; Dong et al, 2015) but hitherto the global proteome has not been examined. In this paper, we investigated the expression of ribosomal proteins and genes using transcriptome, translatome, proteome and phosphoproteome analyses following silencing of the TOR gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the impact of TOR inhibition in Arabidopsis on transcript or metabolite levels (Deprost et al, 2007; Moreau et al, 2012; Caldana et al, 2013; Xiong et al, 2013; Dong et al, 2015) but hitherto the global proteome has not been examined. In this paper, we investigated the expression of ribosomal proteins and genes using transcriptome, translatome, proteome and phosphoproteome analyses following silencing of the TOR gene.…”
Section: Discussionmentioning
confidence: 99%
“…TOR has already been shown to control a vast array of biological processes in plants (Deprost et al, 2007; Caldana et al, 2013; Xiong and Sheen, 2014; Dong et al, 2015) and a link between the TOR complex and protein translation has been evidenced. We have indeed shown earlier that TOR inactivation, either after silencing (Deprost et al, 2007) or by using a TOR inhibitor (Sormani et al, 2007) leads to a decrease in polysome abundance.…”
Section: Introductionmentioning
confidence: 99%
“…1). Several phytohormones, such as jasmonic acid, abscisic acid, salicylic acid, brassinosteroids, and cytokinin, were implicated in cross talk with the TOR signaling pathway (Dong et al, 2015;Kravchenko et al, 2015;Pfeiffer et al, 2016;Zhang et al, 2016;De Vleesschauwer et al, 2017;Song et al, 2017). However, the most prominent growth hormones, auxin and kinetin, are known to promote S6K phosphorylation in cell suspension cultures, which leads to phosphorylation of ribosomal protein S6 (Turck et al, 2004).…”
Section: Upstream Control Of Translation Via Tor Hormone Signaling Tomentioning
confidence: 99%
“…Interestingly, light promotes translation of mRNAs encoding proteins involved in photosynthesis (Petracek et al, 1997;Tang et al, 2003;Floris et al, 2013). Recent data suggested that sugars act not only as energy source, but also as signaling molecules through TOR, maintaining the balance between hormone-promoted growth and carbon availability (Xiong et al, 2013;Dong et al, 2015;Zhang et al, 2016).…”
Section: Light Energy and Sugar Signaling In Translationmentioning
confidence: 99%
See 1 more Smart Citation